En busca del tiempo perdido en la ciudad subyugada: Dora Bruder y el sortilegio de las correspondencias. - Villamía, Luis (Anales de Filología Francesa, 2024)
In his novel, Dora Bruder (1997), the French novelist Patrick Modiano carries out a deep research comparable to those developed in memory studies. The author, in order to reconstruct Dora Bruder´s past, draws on archival materials, deals with survival witnesses interviews and recreates the former places in which Dora Bruder stayed. All this process started when Patrick Modiano was suddenly attracted by a piece of news from an old newspaper. From this perspective, the novel can be analyzed based on the legacy left by Walter Benjamin in the field of memory studies. However, when memory doesn´t leave tracks, Modiano pursues rhetorical strategies, inspired on surrealist literature, that can be described as “memory spells”.